Ultraviolet transmission glass
By optimizing the fluorine content near the glass surface and acid solution etching treatment, the transmittance of the ultraviolet transmittance glass in the deep ultraviolet region is improved, the problem of low transmittance in the prior art is solved, and the detection sensitivity of the flame sensor is improved.
Patent Information
- Application Number
- CN202380040213.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-19
- Filing Date
- 2023-04-25
- Publication Date
- 2024-12-27
AI Technical Summary
The existing ultraviolet transmitting glass has low transmittance in deep ultraviolet areas, especially in areas with wavelengths of 200 to 250 nm, which affects the detection sensitivity of flame sensors.
By optimizing the fluorine (F) content near the glass surface, ensuring that the ratio of the F content x at the depth of 15 μm to the F content y at 1 μm is above 0.8, and an acid solution etching treatment is used to improve Fe3+ near the glass surface. Reduction rate, thereby increasing the transmittance of deep ultraviolet areas.
It achieves a higher transmittance in deep ultraviolet areas than existing products, improving the detection sensitivity and equipment performance of flame sensors.
Smart Images

Figure BDA0005131921070000111
Abstract
Description
Technical Field
[0001] The present invention relates to ultraviolet light transmitting glass. Background Art
[0002] A flame sensor for detecting ultraviolet rays with a wavelength of 185 nm to 260 nm generated by flames has been developed, and a method for detecting fires and flames of combustion devices using the flame sensor has been proposed. For containers and window materials for storing such flame sensors, ultraviolet-transmitting glass with high transmittance in the deep ultraviolet region is used (e.g., Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2017 / 057375 Summary of the invention
[0006] Technical problem that the invention aims to solve
[0007] In flame sensors, ultraviolet-transmitting glass is used as the outer tube, thereby continuously obtaining high detection sensitivity. However, conventional ultraviolet-transmitting glass has a low transmittance, especially in the deep ultraviolet region with a wavelength of 200 to 250 nm, which has become a problem.
[0008] In view of the above circumstances, an object of the present invention is to obtain glass having a higher transmittance in the deep ultraviolet region than conventional products.
[0009] Technical solutions to the problem
[0010] The inventors of the present invention have found that since F is a light element, its content near the surface tends to decrease during the manufacturing process. When the F content near the glass surface is low, the Fe content near the glass surface increases. 3+ It is difficult to be reduced, resulting in reduced transmittance in the deep ultraviolet region.
[0011] That is, the ultraviolet-transmitting glass of the present invention is characterized in that, when the F content at a depth of 15 μm from the glass surface is x (mass %) and the F content at a depth of 1 μm from the glass surface is y (mass %), y / x is 0.8 or more. Here, the "F content" can be measured using a commercially available electron beam microanalyzer (e.g., EPMA-1720H manufactured by Shimadzu Corporation).
[0012] The transmittance (%) of the ultraviolet-transmitting glass of the present invention when the thickness of the glass is 0.5 mm and the wavelength of light is 200 nm is defined as T 200 In the case of T 200≥ 69. Here, the "transmittance when the wavelength of light is 200 nm" can be measured using a commercially available spectrophotometer (for example, UV-3100PC manufactured by Shimadzu Corporation).
[0013] The ultraviolet-transmitting glass of the present invention preferably has a thickness of 0.2 to 2 mm and is in a tubular shape.
[0014] The ultraviolet-transmitting glass of the present invention preferably contains, as a glass composition, SiO2 55% to 75%, Al2O3 1% to 10%, B2O3 10% to 30%, CaO 0 to 5%, BaO 0 to 5%, Li2O+Na2O+K2O 1% to 15%, TiO2 0 to 0.001%, Fe2O3 0 to 0.001%, and F 0.5% to 7%. In addition, "A+B+C" refers to the total amount of component A, component B, and component C. For example, "Li2O+Na2O+K2O" refers to the total amount of Li2O, Na2O, and K2O.
[0015] The ultraviolet-transmitting glass of the present invention is preferably used for a flame sensor.
[0016] The method for producing ultraviolet-transmitting glass of the present invention is characterized in that the glass is formed into a tubular shape and then the tubular glass is immersed in an acid solution for etching.
[0017] Effects of the Invention
[0018] According to the present invention, it is possible to obtain glass having a higher transmittance in the deep ultraviolet region than conventional products. DETAILED DESCRIPTION
[0019] In the ultraviolet-transmitting glass of the present invention, when the F content at a depth of 15 μm from the glass surface is x (mass %) and the F content at a depth of 1 μm from the glass surface is y (mass %), y / x is 0.8 or more, preferably 0.85 or more, and particularly preferably 0.9 or more. If y / x is too small, the Fe contained near the glass surface will 3+ It is difficult to be restored, and the transmittance in the deep ultraviolet region is easily reduced. In addition, the upper limit of y / x is not particularly limited, but is actually below 1.2. In addition, the specific value of y / x is as follows.
[0020] x is preferably 0.5% to 7%, 0.6% to 5%, and particularly preferably 0.7% to 3%. If x is too small, the F content in the glass will decrease, and the Fe content in the glass will decrease. 3+ It is difficult to be reduced, and the transmittance in the deep ultraviolet region tends to decrease. On the other hand, if x is too large, it is difficult to vitrify.
[0021] y is preferably 0.4% to 8.4%, 0.45% to 6%, 0.5% to 5%, and particularly preferably 0.6% to 3%. If y is too small, the F content near the glass surface decreases, and the Fe content near the glass surface decreases. 3+ It is difficult to be reduced, and the transmittance in the deep ultraviolet region is likely to decrease. On the other hand, if y is too large, it is difficult to vitrify.
[0022] In the ultraviolet-transmitting glass of the present invention, the transmittance (%) when the thickness of the glass is 0.5 mm and the wavelength of light is 200 nm is defined as T 200 When T 200 ≥69, especially preferred T 200 ≥70. If the transmittance of the glass is too low when the thickness is 0.5 mm and the wavelength of light is 200 nm, it is difficult for ultraviolet light to be transmitted, and the performance of the mounted light source and equipment is likely to be reduced.
[0023] In the ultraviolet-transmitting glass of the present invention, the transmittance (%) when the thickness of the glass is 0.5 mm and the wavelength of light is 220 nm is defined as T 220 In the case of T 220 ≥79, especially preferred T 220 ≥80. If the transmittance of the glass is too low when the thickness is 0.5 mm and the wavelength of light is 220 nm, it is difficult for ultraviolet light to be transmitted, and the performance of the mounted light source and equipment is likely to be reduced.
[0024] In the ultraviolet-transmitting glass of the present invention, the transmittance (%) when the thickness of the glass is 0.5 mm and the wavelength of light is 250 nm is defined as T 250 In the case of T 250 ≥87, especially preferred T 250 ≥88. If the transmittance of the glass is too low when the thickness is 0.5 mm and the wavelength of light is 250 nm, it is difficult for ultraviolet light to pass through, and the performance of the mounted light source and equipment is likely to be reduced.
[0025] The strain point of the ultraviolet-transmitting glass of the present invention is preferably 400°C or higher, 410°C or higher, and particularly preferably 415°C or higher. When the strain point of the ultraviolet-transmitting glass is too low, for example, when a functional film is formed on the surface, the glass is prone to undesirable deformation in the high-temperature film-forming process. It should be noted that the upper limit of the strain point is not particularly limited, but is actually below 600°C.
[0026] The softening point of the ultraviolet-transmitting glass of the present invention is preferably 850°C or less, 800°C or less, 750°C or less, and particularly preferably 700°C or less. If the softening point is too high, it is difficult to reheat the glass. It should be noted that the lower limit of the softening point is not particularly limited, but is actually 600°C or more.
[0027] The viscosity of the ultraviolet transmission glass of the present invention is 10 2.5 dPa·s is 1540°C or lower, preferably 1520°C or lower, more preferably 1500°C or lower, and particularly preferably 1480°C or lower. 2.5 dPa·s, the load on the glass melting furnace increases, the melting property decreases, and the manufacturing cost of the glass tends to increase. 2.5 dPa·s” can be measured by the platinum ball pulling method. It should be noted that 10 2.5 The lower limit of the temperature at dPa·s is not particularly limited, but is actually 1300° C. or higher.
[0028] The average linear thermal expansion coefficient of the ultraviolet-transmitting glass of the present invention in the temperature range of 30°C to 380°C is preferably 30×10 -7 / ℃ or more, particularly preferably 35×10 -7 / ℃ or more, and preferably 95×10 -7 / ℃ or less, particularly preferably 80×10 -7 / °C or less. If the average linear thermal expansion coefficient is too low, it will be difficult to match the thermal expansion coefficients of various components such as sensor terminals. On the other hand, if the average linear thermal expansion coefficient is too high, the glass is easily broken by thermal shock.
[0029] The liquidus temperature of the ultraviolet-transmitting glass of the present invention is preferably 1120°C or less, 1100°C or less, 1080°C or less, 1050°C or less, 1000°C or less, 950°C or less, 900°C or less, and particularly preferably 850°C or less. The viscosity at the liquidus temperature is preferably 10 4.0 dPa·s or more, 10 4.3 dPa·s or more, 10 4.5 dPa·s or more, 10 4.8 dPa·s or more, 10 5.1 dPa·s or more, 10 5.3 dPa·s or more, particularly preferably 10 5.5 dPa·s or more. In this way, the devitrification resistance is improved, and forming by a down-draw method, particularly an overflow down-draw method, is easy, so that it is easy to produce glass of a desired shape.
[0030] The Young's modulus of the ultraviolet-transmitting glass of the present invention is preferably 40 GPa or more, particularly preferably 45 GPa or more. If the Young's modulus is too low, the glass is difficult to maintain rigidity in the conveying line in the manufacturing process of the equipment, and the glass is easily deformed, warped, or broken.
[0031] The ultraviolet-transmitting glass of the present invention preferably contains, as a glass composition, by mass%, the following: SiO2 55% to 75%, Al2O3 1% to 10%, B2O3 10% to 30%, CaO 0 to 5%, BaO0 to 5%, Li2O+Na2O+K2O 1% to 15%, TiO2 0 to 0.001%, Fe2O3 0 to 0.001%, and F 0.5% to 7%.
[0032] The reasons for limiting the content of each component as described above are as follows: In the description of the content of each component, % means mass % unless otherwise specified.
[0033] SiO2 is the main component that forms the glass skeleton. The content of SiO2 is preferably 55% to 75%, 58% to 70%, and particularly preferably 65% to 69%. If the content of SiO2 is too little, Young's modulus and acid resistance are likely to decrease. On the other hand, if the content of SiO2 is too much, the high-temperature viscosity becomes high, the solubility is likely to decrease, and devitrified crystals such as cristobalite are likely to precipitate, and the liquidus temperature is likely to rise.
[0034] Al2O3 is a component that increases Young's modulus and suppresses phase separation and devitrification. The content of Al2O3 is preferably 1% to 10%, 2% to 9%, and particularly preferably 3% to 8%. If the content of Al2O3 is too little, the Young's modulus is likely to decrease, and the glass is likely to phase separate and devitrify. On the other hand, if the content of Al2O3 is too much, the high-temperature viscosity increases and the solubility is likely to decrease.
[0035] B2O3 is a component that improves solubility and resistance to devitrification, and is also a component that improves the susceptibility to damage and increases strength. The content of B2O3 is preferably 10% to 30%, 13% to 28%, and particularly preferably 15% to 25%. If the content of B2O3 is too little, the solubility and resistance to devitrification are likely to decrease, and the resistance to hydrofluoric acid-based liquid is likely to decrease. On the other hand, if the content of B2O3 is too much, the Young's modulus and acid resistance are likely to decrease.
[0036] CaO is a component that reduces high temperature viscosity and improves melting properties. In addition, among alkaline earth metal oxides, CaO is a component that reduces the cost of raw materials because the raw materials introduced are relatively cheap. The content of CaO is preferably 0 to 5%, 0.01% to 1%, and particularly preferably 0.1% to 0.8%. If the content of CaO is too high, the glass is prone to devitrification.
[0037] BaO is a component that improves the resistance to devitrification. The content of BaO is preferably 0 to 5%, 0.1 to 3%, and particularly preferably 0.5 to 1.5%. If the content of BaO is too high, the glass is likely to devitrify.
[0038] Li2O, Na2O and K2O are alkali metal oxide components that reduce high temperature viscosity, significantly improve solubility, and contribute to the initial melting of glass raw materials. The content of Li2O+Na2O+K2O is preferably 1% to 15%, 2% to 10%, and particularly preferably 3% to 6%. If the content of Li2O+Na2O+K2O is too little, the solubility is likely to decrease. On the other hand, if the content of Li2O+Na2O+K2O is too much, the thermal expansion coefficient may become unduly high.
[0039] Li2O is a component that reduces high temperature viscosity, significantly improves solubility, and contributes to the initial melting of glass raw materials. The content of Li2O is preferably 0-5%, 0-3%, and particularly preferably 0.1%-1.2%. If the content of Li2O is too high, the glass is prone to phase separation.
[0040] Na2O is a component that reduces high temperature viscosity, significantly improves solubility, and contributes to the initial melting of glass raw materials. In addition, it is a component used to adjust the thermal expansion coefficient. The content of Na2O is preferably 0-10%, 0-8%, 1%-5%, and particularly preferably 1%-3%. If the content of Na2O is too much, the thermal expansion coefficient may become unduly high.
[0041] K2O is a component that reduces high temperature viscosity, significantly improves solubility, and contributes to the initial melting of glass raw materials. In addition, it is a component used to adjust the thermal expansion coefficient. The content of K2O is preferably 0-10%, 0.1%-5%, and particularly preferably 0.5%-3%. If the content of K2O is too much, the thermal expansion coefficient may become unduly high.
[0042] TiO2 is a component that reduces the transmittance in the deep ultraviolet region. The content of TiO2 is preferably below 0.001%, below 0.0008%, and particularly preferably 0.0001 to 0.0006%. If the content of TiO2 is too much, the glass will be colored and the transmittance in the deep ultraviolet region will be easily reduced.
[0043] Fe2O3 is a component that reduces the transmittance in the deep ultraviolet region. The content of Fe2O3 is preferably 0.001% or less, 0.0001% to 0.0009%, and particularly preferably 0.00001% to 0.0008%. If the content of Fe2O3 is too high, the glass will be colored and the transmittance in the deep ultraviolet region will be easily reduced.
[0044] The Fe ions in iron oxide are Fe 2+ or Fe 3+ The state exists. If Fe 2+ If the ratio of Fe is too small, the transmittance in deep ultraviolet light is likely to decrease. Therefore, Fe in the iron oxide contained in the ultraviolet-transmitting glass of the present invention is 2+ / (Fe 2++Fe 3+ ) is preferably at least 0.1, at least 0.2, at least 0.3, at least 0.4, and particularly preferably at least 0.5.
[0045] F is the Fe contained in the glass 3+ It is a component that reduces and improves the transmittance in the deep ultraviolet region. In addition, it is a component that reduces viscosity and improves solubility. The F content is preferably 0.5% to 7%, 0.6% to 5%, and particularly preferably 0.7% to 3%. When the F content is too low, it is difficult to obtain the above effect. On the other hand, if the F content is too high, it is difficult to vitrify.
[0046] In addition to the above-mentioned components, the following components may be introduced.
[0047] SrO is a component that improves the resistance to devitrification. The content of SrO is preferably 0 to 7%, 0 to 5%, 0 to 3%, and particularly preferably 0 to 1%. If the content of SrO is too high, the glass is likely to devitrify.
[0048] ZrO2 is a component that improves acid resistance, but if it is contained in a large amount in the glass composition, the glass is prone to devitrification. Therefore, the content of ZrO2 is preferably 0.1% or less, 0.001% to 0.02%, and particularly preferably 0.0001% to 0.01%.
[0049] MoO3 is a component contained as an impurity from the furnace during production, but if it is contained in large quantities in the glass composition, it is possible to reduce the transmittance in the deep ultraviolet region. Therefore, the content of MoO3 is preferably less than 0.05%, 0.005% to 0.001%, and particularly preferably 0.0001% to 0.0005%.
[0050] The shape of the ultraviolet-transmitting glass of the present invention can be arbitrarily set. For example, the shape of the ultraviolet-transmitting glass of the present invention can be a flat plate, a curved plate, a straight tube, a curved tube, a rod, a sphere, a container, or a block.
[0051] In order to be suitable for flame sensor use, the thickness of the ultraviolet transmissive glass is preferably 0.2 to 2 mm, particularly preferably 0.25 to 1.9 mm, and is preferably in a tubular shape such as a straight tube or a curved tube. It should be noted that, in general, the thicker the glass, the lower the ultraviolet transmissivity, but the ultraviolet transmissive glass of the present invention has a high transmissivity in a wavelength region below 250 nm, so even if the thickness is increased compared to existing products, it is possible to maintain a high transmissivity in this wavelength region.
[0052] The surface roughness Ra of the surface of the ultraviolet light-transmitting glass of the present invention is preferably 10 nm or less, 9 nm or less, 8 nm or less, 7 nm or less, 6 nm or less, 5 nm or less, 4 nm or less, 3 nm or less, 2 nm or less, and particularly preferably 1 nm or less. If the surface roughness Ra of the surface is too large, there is a tendency for the transmittance to decrease during deep ultraviolet light.
[0053] The ultraviolet-transmitting glass of the present invention can be produced, for example, by mixing various glass raw materials to obtain a glass batch, then melting the glass batch, clarifying and homogenizing the obtained molten glass, and molding it into a predetermined shape.
[0054] In the method for producing ultraviolet-transmitting glass of the present invention, it is preferred to use a reducing agent as part of the glass raw material. 3+ As the reducing agent, materials such as wood powder, carbon powder, metal aluminum, metal silicon, and aluminum fluoride can be used, among which metal silicon and aluminum fluoride are preferred.
[0055] In the method for producing ultraviolet-transmitting glass of the present invention, metal silicon is preferably used as a part of the glass raw material, and its addition amount is preferably 0.001 mass % to 3 mass %, 0.005 mass % to 2 mass %, 0.01 mass % to 1 mass %, and particularly preferably 0.05 mass % to 0.75 mass %. If the addition amount of metal silicon is too small, the Fe contained in the glass 3+ If it is not reduced, the transmittance under deep ultraviolet light is likely to decrease. On the other hand, if the amount of metal silicon added is too much, the glass tends to be colored brown.
[0056] In addition, aluminum fluoride (AlF3) is also preferably used as part of the glass raw material, and its addition amount is preferably 0.01 mass% to 2 mass%, 0.05 mass% to 1.5 mass%, and particularly preferably 0.3 mass% to 1.5 mass% relative to the total mass of the glass batch material in terms of F conversion. If the addition amount of aluminum fluoride is too small, the Fe contained in the glass will 3+ If it is not reduced, the transmittance in deep ultraviolet light is likely to decrease. On the other hand, if the amount of aluminum fluoride added is too much, the F gas may remain in the glass in the form of bubbles.
[0057] In the manufacturing method of the ultraviolet-transmitting glass of the present invention, when the ultraviolet-transmitting glass is formed into a flat plate shape, it is preferably formed using a down-draw method or an overflow down-draw method. The overflow down-draw method is a method for forming a glass sheet by causing molten glass to overflow from both sides of a heat-resistant groove-shaped structure, and causing the overflowing molten glass to merge at the lower top of the groove-shaped structure while extending downward to form. In the overflow down-draw method, the surface of the glass sheet that should become the surface does not contact the groove-shaped refractory, and is formed in a free surface state. Therefore, it is easy to make a thin glass sheet, and even if the surface is not ground, the thickness deviation can be reduced. As a result, the manufacturing cost of the glass sheet can be reduced. In addition, the structure and material of the groove-shaped structure are not particularly limited as long as the desired size and surface accuracy can be achieved. In addition, when performing downward extension forming, the method of applying force is not particularly limited. For example, a method of extending by rotating a heat-resistant roller having a sufficiently large width in a state of contact with the glass can be adopted, and a method of extending by contacting a plurality of pairs of heat-resistant rollers only near the end face of the glass can also be adopted.
[0058] In the method for manufacturing ultraviolet-transmitting glass of the present invention, when the ultraviolet-transmitting glass is formed into a tube, it is preferably formed by a down-draw method, a Belleau method, a Daner method, etc. The Daner method is a method of forming a glass tube by making molten glass flow down and winding it around the upper end side of a heat-resistant sleeve-shaped structure arranged obliquely, and stretching the molten glass flowing down to the lower end side.
[0059] As a forming method, in addition to the above, for example, a slot down-draw method, a re-draw method, a float method, etc. can also be adopted.
[0060] In the manufacturing process of ultraviolet-transmitting glass, the F content of the surface layer of the glass is sometimes easily reduced. In this case, after the glass is formed, the glass is immersed in an acid solution for etching to remove the surface layer with reduced F content, thereby increasing the F content near the surface of the glass. It should be noted that as the acid used in the etching process, 3% to 50% by mass of nitric acid, hydrofluoric acid, sulfuric acid, hydrochloric acid, or a mixed acid with an acid concentration of 3% to 50% by mass and at least two of the above acids can be used. The immersion time is preferably 1 minute or more, 3 minutes or more, and particularly preferably 5 minutes or more. If the immersion time is too short, the etching becomes insufficient, and the F content near the surface of the glass may not increase. The upper limit of the immersion time is not particularly limited, and in reality it is less than 20 minutes. The temperature of the acid is preferably 20°C or more, 25°C or more, and particularly preferably 30°C or more. If the temperature of the acid is too low, the etching becomes insufficient, and the F content near the surface of the glass may not increase. The upper limit of the temperature of the acid is not particularly limited, and in reality it is less than 95°C. It should be noted that the surface layer portion in which the F content is reduced may be removed by physical grinding or the like.
[0061] Example
[0062] Hereinafter, the present invention will be described based on examples. In addition, the following examples are only for illustration. The present invention is not limited in any way by the following examples.
[0063] Table 1 shows Examples (Sample Nos. 1 to 5) of the present invention and a Comparative Example (Sample No. 6).
[0064] [Table 1]
[0065]
[0066] First, a glass batch prepared by blending the glass raw materials shown in the table so as to obtain the glass composition shown in the table was placed in a platinum crucible and melted at 1600° C. for 6 hours.
[0067] The obtained molten glass was stirred and homogenized using a platinum stirrer. Next, the molten glass was poured onto a carbon plate and formed into a flat plate shape, then annealed at a rate of 3°C / min from a temperature about 20°C higher than the annealing point to room temperature, and then etched under the conditions shown in the table.
[0068] The transmittance of each sample obtained was measured. The transmittance is a value obtained by measuring the spectral transmittance in the thickness direction using a double-beam spectrophotometer (UV-3100PC manufactured by Shimadzu Corporation). As the measurement sample, a sample in which both sides were polished to an optical polished surface (mirror surface) with the thickness described in Table 1 was used. It should be noted that the surface roughness Ra of the surface of these measurement samples was measured by AFM, and the result was that it was 0.5 to 1.0 nm in the measurement area of 10 μm×10 μm.
[0069] In addition, for each sample obtained, the F content x (mass %) at a depth of 15 μm from the glass surface and the F content y (mass %) at a depth of 1 μm from the glass surface were measured by performing line analysis on the cross section of the sample using an electron beam microanalyzer (EPMA-1720H manufactured by Shimadzu Corporation).
[0070] As can be seen from the table, in samples No. 1 to 5 where y / x is 0.81 or more, the transmittance of ultraviolet light with a wavelength of 200nm to 250nm is high. On the other hand, in sample No. 6 where y / x is as small as 0.71, the transmittance of ultraviolet light with a wavelength of 200nm to 250nm is low. In addition, it can be seen that the larger y / x is, the higher the transmittance of ultraviolet light with a wavelength of 200nm to 250nm is.
[0071] It should be noted that, in the above-mentioned embodiment, the molten glass is flowed out and formed into a flat plate shape, but in the case of industrial-scale production, it is preferably formed into a flat plate shape by overflow down-drawing method etc., and is provided for use in the state of not grinding the two surfaces. In addition, when formed into a tubular shape, it is preferably formed into a tubular shape by down-drawing method, Dana method etc.
Claims
1. A UV-transmitting glass, characterized in that: When x is the content of F in a depth of 15 μm from the glass surface and y is the content of F in a mass % from the glass surface at a depth of 1 μm, y / x is 0.8 or more.
2. The ultraviolet-transmitting glass according to claim 1, characterized in that: The transmittance in % when the thickness of the glass is 0.5 mm and the wavelength of light is 200 nm is defined as T 200 When T 200 ≥69.
3. The ultraviolet-transmitting glass according to claim 1 or 2, characterized in that: The thickness of the ultraviolet light transmitting glass is 0.2-2.0 mm, and the ultraviolet light transmitting glass is in a tubular shape.
4. The ultraviolet-transmitting glass according to claim 1 or 2, characterized in that: The glass composition includes, by mass%, SiO2 55% to 75%, Al2O3 1% to 10%, B2O3 10% to 30%, CaO 0 to 5%, BaO 0 to 5%, Li2O+Na2O+K2O 1% to 15%, TiO2 0 to 0.001%, Fe2O3 0 to 0.001%, and F 0.5% to 7%.
5. The ultraviolet-transmitting glass according to claim 1 or 2, characterized in that: The ultraviolet light transmitting glass is used for flame sensors.
6. A method for manufacturing ultraviolet-transmitting glass, characterized in that: After the glass is formed into a tubular shape, the tubular glass is immersed in an acid solution for etching.